- PENCEMARAN LAUT KAPAL MV EVER JUDGER PANAMA DI BALIKPAPAN BERDASARKAN MARPOL CONVENTION : - - Alvin Wibisono; Ayu Nrangwesti (Fakultas Hukum Universitas Trisakti, 2023)
The 2018 oil spill in Balikpapan began with a miscommunication by the Panama-flagged ship MV Ever Judger to drop the anchor, but the length of the anchor that was lowered exceeded the instructions, causing the anchor to damage the oil pipeline leading to Pertamina's oil processor. Damage to the pipeline caused an explosion, which killed several people. According to Indonesian law and court decisions, the ship, which is also the perpetrator, faces criminal charges for environmental pollution. The problem in this thesis is determining how to resolve the case of the ship MV Ever Judger, which caused an oil leak in Balikpapan based on the MARPOL Convention, and what the ship's captain is responsible for. The research method used is normative juridical, analytical descriptive, and deductive in nature. Thestudy's result, discussion andconclusion is the perpetrators were convicted under Indonesian legal jurisdiction and proven to have violated the MARPOL Convention. The perpetrators were punished under Indonesian criminal law in accordance with the MARPOL Convention, which states that violators must be punished in accordance with the laws of the country where the pollution occurred.